Faktor-Faktor yang Mempengaruhi Audit Delay - Wirakusuma, Made Gede; Widyantari, Ni Putu (E-Jurnal Akuntansi, 2012)
Improved audit of financial statements will evolve along with the rapid development of the capital market in Indonesia. The length of time to complete the audit (audit delay) in any company will affect on the timeliness of the publication of the financial statements. The purpose of this study was to determine the factors that affect audit delay the manufacturing companies listed on the Indonesia Stock Exchange the period 2008-2011. This study uses 39 manufacturing companies listed in the Indonesia Stock Exchange the period 2008-2011 using purposive sampling method in determining the number of samples and non-participant observation methods in collection data and using multiple linear regression analysis techniques in analyzing the data. Based on the discussion of this study concluded that only the size of public accounting office are influential and significant to the audit delay in manufacturing companies, while firm size, solvency, profitability, and the auditor's opinion does not affect and not significant impact to the audit delay on manufacturing companies listed on the Indonesia Stock Exchange the period 2008-2011. Keywords: firm size, solvency, profitability, auditor's opinion, the size of public accounting office , audit delay
Keywords: firm size, solvency, profitability, auditor' s opinion, the size of public accounting office, audit delay